Evaluation of fillet welds properties performed by cold metal transfer robotic metal active gas welding technology - Brezinová, Janette; Hašuľ, Ján (Transport, 2023)
The article is the result of research evaluating the quality of fillet welds used in the production of rear seat backrests for passenger cars and manufactured robotically by Cold Metal Transfer (CMT) robotic Metal Active Gas (MAG) welding. When robotizing the process, parameters such as the speed of the process itself, accuracy and quality of the welded joints are important. Dual-phase ferritic-martensitic steel HCX 590X was used for the experiment and four weld nodes were evaluated. The quality of welded joints was evaluated by visual and capillary methods. Based on the metallographic analysis, the weld depth of the weld root was evaluated. The measured values were subsequently processed by statistical method ANalysis Of Variance (ANOVA). The research confirmed that the final quality of the welds depends on the depth of the weld root weld into the Base Material (BM). This parameter has the greatest effect on the welds made and results in the entire product being taken out of service.